The Scarlet Thread: Robert Lax and Charity, 1941–1945 - Benson, Joshua (The catholic historical review, 2025)
Robert Lax is best known for his friendship with Thomas Merton but is himself an important figure within twentieth-century Catholicism. Recently, a series of publications has made Lax's life and literary legacy better known. At least one period in Lax's life admits of further study: the years 1941–1945. During this period, Lax met Catherine De Hueck (Doherty), worked at Friendship House Harlem, met Paul Hanly Furfey and utilized him as a spiritual advisor, became a Roman Catholic, and began but did not finish a dissertation on charity as the form of the virtues in Thomas Aquinas under the direction of the important German-born philosopher Helmut Kuhn. Previously unknown documents allow a better appreciation of all these events in Lax's life and their connection to his later life and writing.